Experience of Wellness Recovery Action Planning in Self-Help and Mutual Support Groups for People with Lived Experience of Mental Health Difficulties. (9th January 2013) - Pratt, Rebekah; MacGregor, Andy; Reid, Susan; Given, Lisa
Abstract : The main aim of this research was to assess the relevance and impact of wellness recovery action planning (WRAP) as a tool for self-management and wellness planning by individuals with mental health problems from pre-existing and newly formed groups, where the possibilities for continued mutual support in the development of WRAPs could be explored. Interviews and focus groups were conducted and pre-post recovery outcome measures completed (Recovery Assessment Scale and Warwick Edinburgh Mental Well Being Scale). 21 WRAP group participants took part in the research. The WRAP approach, used in groups and delivered by trained facilitators who could also share their lived experience, was very relevant and appeared to have a positive impact on many of the participants. The impact on participants varied from learning more about recovery and developing improved self-awareness to integrating a WRAP approach into daily life. The apparent positive impact of WRAP delivered in the context of mutual support groups indicates that it should be given serious consideration as a unique and worthwhile option for improving mental health. WRAP groups could make a significant contribution to the range of self-management options that are available for improving mental health and well-being.